MNGI-07. THE ANAPLASTIC MENINGIOMA INTERNATIONAL CONSORTIUM (AMICo) RETROSPECTIVE STUDY OF TREATMENT AND OUTCOME OF PATIENTS WITH ANAPLASTIC MENINGIOMAS. (5th November 2018) - di Bonaventura, Rina; Young, Adam; Zakaria, Rasheed; Champeaux, Charles; Foo, Aaron; Tonn, Jörg-Christian; McMurran, Christopher; Yeo, Tseng Tai; Kirsch, Matthias; Afshari, Fardad; Florian, Stefan; Rossi, Marco; et al.
Abstract: Anaplastic meningiomas are rare, comprising only 1–2% of all meningiomas, and limited data on its natural history and response to treatment. An international retrospective study using 2016 Classification of the Tumours of the CNS was used to identify grade 3 meningiomas. Anonymised clinical and radiological data were collected in a uniform manner from 21 centres. RESULTS: 355 patients were identified to have an anaplastic meningioma. 57% cases arose de novo and 43% were progressed from lower grade; 20% directly from grade 1, 15% from grade 1 via grade 2 and 65% from grade 2. Female predominated among de novo and males among the progressive cases, with M/F ratios 0.8 and 1.4, respectively (p=0.02). De novo tumours were, on average, larger than progressive (51cc and 27cc, respectively; p=0.002). De novo cases predominated in sphenoid wing and ventricular locations, while progressive cases predominated in anterior fossa midline locations. The median survival of patient from the first diagnosis of anaplastic meningioma (index surgery) was 99 and 30 months for de novo and progressive cases, respectively (p<0.0001). Independent factors for survival were degree of resection (p=0.23) and administration of radiotherapy (p<0.001). Among the progressive anaplastic meningiomas, the longest survival was achieved in patients who received radiotherapy both before and after the index surgery. Those receiving radiotherapy only after lived longer than those who received radiotherapy before the index surgery. Those who received no radiotherapy had shortest survival. The difference in growth between surgery only and surgery and radiotherapy groups was significant (17.6%/month versus 5.3%/month; p = 0.038). Here in we present the largest cohort of patients with anaplastic meningiomas allowing detailed analysis of natural history and response to treatment in de novo and progressive anaplastic meningiomas.